ASPEK HUKUM FINTECH SYARIAH UNTUK PENINGKATAN FINDRISING WAKAF UANG DI INDONESIA - Siska Lis Sulistiani (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2019)
This study aims to determine the legal aspects of financial technology related to endowments in making finding money endowments in indonesia. Waqf money in indonesia is very potential, if maximized by all aspects including legal instruments and technological advances in socializing the urgency and benefits of waqf for the economic, social and religious progress of the community. The method used is a normative juridical method through primary, secondary and tertiary legal data relating to fintech and endowments of money. The findings of this study are that the development of legal related to waqf fintech can be done from both national law and islamic law in finding endowments for benefit as long as they maintain harmony and waqf requirements, and maintain the core of waqf assets collected to be developed in other more useful forms.